Towards Understanding Benefit Sharing between Extractive Industries and Indigenous/Local Communities in the Arctic - Maria S. Tysiachniouk (Resources, 2020)
The aim of this Special Issue is to provide a comprehensive view of the benefit sharing and compensation mechanisms for the Indigenous Peoples and local communities in the Arctic and sub-Arctic regions due to industrial resource extraction. The papers cover the following topics: (1) Benefit-sharing frameworks in the Arctic. (2) Corporate social responsibility standards and benefit sharing by extractive industries in the Arctic. (3) Benefit sharing and international and national legislation. (4) The practice of implementing legislation to support Indigenous and local interests. (5) The methodologies for assessing compensation to Indigenous communities from extractive industries.